AB0409 Prevalence of nasal colonization by staphylococcus aureus in patients with rheumatoid arthritis. (23rd January 2014) - Ricse, M.; Albert, G.; Narváez, J.; Nolla, J.M.; Domínguez, M.A.; Gόmez, C.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an increased risk of developing infections caused by Staphylococcus aureus . This bacterium is responsible of up to 80% of septic arthritis in patients with RA. The risk of infection seems to be even greater in patients treated with biologics, administered alone or in combination with methotrexate. In the general population, the prevalence of nasal colonization is 30%, and this plays an important role in the pathogenesis of staphylococcal infection: nasal carriers of Staphylococcus aureus have an increase of the risk of infection between 2 and 12 times. Objectives: Determine the prevalence of nasal Staphylococcus aureus in patients with RA and its relationship to the treatment of the disease. Methods: One hundred thirty-one patients with RA were included prospectively in a cross-sectional study. They were diagnosed according to the classification criteria of ACR/EULAR 2010 and monitored regularly in the outpatient clinics of a university hospital. The exclusion criteria for sample selection were: 1) to have received antibiotic treatment during the previous month and 2) to have been hospitalized for three months before the sample collection. We reviewed the medical record and collected data about: 1) sex, age and evolution time of RA, 2) RF andantiPCC, 3) presence of erosions, 4) DAS28 and 5) treatment provided at the time of study: glucocorticoids, DMARDs or biological treatment. A sample of nasal secretion was collected by swab from all patients from both anterior nostrils and was later referred to the Microbiology Department for processing. When the microorganism was isolated, the degree of colonization was quantified as presence of low, moderate or abundant colonies. Results: We included 131 patients (60±12 years, 32 (24%) men). The average age was 60±12 years and mean disease evolution 12±8 years. 71% of patients HAD positive RF and 68%, the antiPCC. 65% had joint erosions. The average DAS28 was 2.7±1.2. 66% of the patients were receiving treatment with glucocorticoids; the most frequent DMARDs were methotrexate, leflunomide or a combination of both (82%); 47% were receiving biological treatment. Nasal colonization by S. aureus was 35% (9% few colonies, 30% moderate colonies and 61% abundant colonies), all sensitive to oxacilin/mupirocin. By gender, the prevalence of colonization was 25% in men and 38% in women (p: ns). Patients with positive antiPCC showed a higher prevalence of colonization than the negative antiPCC (40% vs 20%; p<0.05). The prevalence of colonization in patients treated with glucocorticoids was 31%; in those treated with methotrexate and/or leflunomide, 36%; and in biological treated patients, 37%: infliximab, 47% (n: 19); etanercept, 20% (n: 5); adalimumab, 33% (n: 9); rituximab, 22% (n: 9); abatacept, 50% (n: 6); tocilizumab, 31% (n: 13) y certolizumab, 100% (n: 1). Conclusions: The prevalence of Sthaphylococcus aureus nasal colonization in patients with RA in this series appears superior to that of the general population. The results suggest that some of the biological treatments can determine a higher prevalence of colonization. Disclosure of Interest: None Declared